Evolutionary Genomics of Staphylococcus aureus Reveals Insights into the Origin and Molecular Basis of Ruminant Host Adaptation - SMYTH, CYRIL JAMES (Oxford University Press, 2010)
Phenotypic biotyping has traditionally been used to differentiate bacteria occupying distinct ecological niches such as host species. For example, the capacity of Staphylococcus aureus from sheep to coagulate ruminant plasma, reported over 60 years ago, led to the description of small ruminant and bovine S. aureus ecovars. The great majority of small ruminant isolates are represented by a single, widespread clonal complex (CC133) of S. aureus, but its evolutionary origin and the molecular basis for its host tropism remain unknown. Here, we provide evidence that the CC133 clone evolved as the result of a human to ruminant host jump followed by adaptive genome diversification. Comparative whole-genome sequencing revealed molecular evidence for host adaptation including gene decay and diversification of proteins involved in host?pathogen interactions. Importantly, several novel mobile genetic elements encoding virulence proteins with attenuated or enhanced activity in ruminants were widely distributed in CC133 isolates, suggesting a key role in its host-specific interactions. To investigate this further, we examined the activity of a novel staphylococcal pathogenicity island (SaPIov2) found in the great majority of CC133 isolates which encodes a variant of the chromosomally encoded von Willebrand-binding protein (vWbpSov2), previously demonstrated to have coagulase activity for human plasma. Remarkably, we discovered that SaPIov2 confers the ability to coagulate ruminant plasma suggesting an important role in ruminant disease pathogenesis and revealing the origin of a defining phenotype of the classical S. aureus biotyping scheme. Taken together, these data provide broad new insights into the origin and molecular basis of S. aureus ruminant host specificity.
PUBLISHED
Keywords: Immunology; Genetics; Staphylococcus aureus